Relationship marketing in tourism in the era of Industry 4.0 / Murni Yusoff - Yusoff, Murni (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
Relationship marketing (RM) is a paradigm in marketing products and services by using the relationship as the primary tool. The RM paradigm was introduced in the 1990s has been practically implemented in the services and manufacturing industries. One of the popular services industries that implement RM is tourism. By building bonds with customers that are also known as tourists, the outcome for business is believed to be positive. The larger the number of bonds developed, the stronger the relationship will be more effective. However, the industrial revolution evolved. In the present era of Industrial Revolution 4.0, the business marketing shift from conventional to digital marketing. The conventional marketing refers to RM that involves human touch and physical interaction while digital marketing refers to the technologies used as resources to market products and services. The questions might be raised, does the spirit of conventional marketing like RM is getting faded? Does the new revolution industry make RM less attractive to be practised as the new technology in the industry requires more digital application? Therefore, this paper attempts to explore the relevancy of RM in tourism in the current era. The data collected by using document research and analyzed by qualitative content analysis. The findings show that there is the relevancy of RM to be practised as the marketing approach in the tourism industry. Although digital marketing (DM) is vital to attract customers, RM purpose is to retain and turn the customers to loyal customers through the bonds developed. Therefore, the integration of RM and DM in three approaches are identified to be applied in the tourism industry.